Temptation goods, state-dependent patience and wealth inequality - Amaral, Felipe Bordini do (2021)
The present work builds upon the concept of "temptation goods" as established by Banerjee and Mullainathan (2010): consumption goods that are valued only when consumed, not before. This temptation preference is taken into a general equilibrium, overlapping generations environment in order to assess the difference in its theoretical predictions on aggregate measures, in comparison to traditional preferences. The model is disciplined using detailed Brazilian consumption survey data. The calibration results supports the hypothesis of "declining temptation". Adding minimum consumption a la Stone-Geary improves fit to data. An income process with non linear persistence and non log-normal innovations is constructed. This richer income process features some important aspects not considered in canonical models, such as higher persistence of high income agents and a build-up around minimum wage levels. Results from the calibrated model indicate that, although decreasing, temptation’s importance is concentrated in extremely low levels of consumption and results in effectively no impact to predicted wealth distribution. However, when it comes to evaluating perceived patience of specific agents, failing to consider the temptation mechanism results in higher dispersion and left-skewness of the time discount parameter.